Hubungan Kepadatan Hunian dan Kualitas Fisik Rumah Desa Penda Asam Barito Selatan - Darmiah Darmiah; Imam Santoso; Maharso Maharso (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2015)
Abstract: Residential density and housis physical quality in the Penda Asam Village of district South Barito 2014. A house that doesn’t meet the physical requirements can cause immune deficiencies so that the diseases so easily affected. This research aims to know the physical quality’s house and residential density in the Penda Asam’s village of South hamlet subdistrict South Barito regency 2014. This research design was cross sectional with observation method, and measurement. The research population is 195 head of family with 51 houses sample. Data analysis was based on Kepmenkes RI No.829/Menkes/SK/VII/1999 about health housing requirements. The research result showed physical quality’s house: the kind of zinc roof as many as 35 houses 68,6% and 11,8% multiroof. The lighting eligible as 74,5%; ineligible as 25,5%, the temperature eligible as 7,8%; ineligible as 92,2%, the humidity eligible as 17,6%; ineligible as 82,4%, the residential density not solid’s category as 45%; solid’s category as 55%. The effort to overcome the problem: open the window in the morning, keep the ventilation system so that air circulation can be fluently, do reforestation around the house so that the environment condition becomes cool. Keywords: Residential Density, House Physical (the kind of roof; lighting; temperature; humidity)